The relationship between pregnancy-related anxiety, trait anxiety, and internet use in pregnant women: a cross-sectional study - Çelenk, Yusuf Bilal; Yakar, Burkay (My University, 2024)
Introduction: Pregnancy-related anxiety leads to some negative maternal and fetal complications. Determining prenatal and natal anxiety and associated factors can help identify high-risk women who need intervention during pregnancy and develop early intervention strategies. The aim of this study is to determine pregnancy-related, and trait anxiety in the prenatal period and its affecting factors. Methods: This cross-sectional and descriptive study was conducted with 245 pregnant women in the obstetrics clinic of a tertiary healthcare institution between March and August 2022. The sociodemographic, obstetric, and internet use of the participants were questioned. Pregnancy-related anxiety was assessed by using Pregnancy-Related Anxiety Questionnaire-Revised-2 (PRAQ-R2), and trait anxiety was assessed by using State–Trait Anxiety Inventory-I (STAI-II). Results: Pregnant women’s mean scale score for STAI (trait) was 45.54 ± 6.32, for PRAQ-R2 total score was 27.80 ± 8.32, for PRAQ- Fear of giving birth score was 10.12 ± 3.92, PRAQ- Worries about bearing a physically or mentally handicapped child score was 10.44 ± 4.11, and PRAQ- Concern about own appearance score was 7.24 ± 2.86. Pregnancy-related Anxiety Scale score was higher in nulliparous than multiparous (p=0.002) and 30-35 age groups than others (p=0.014). Having a chronic disease is related to a higher anxiety score (p=0.028). Trait anxiety scores were higher in nulliparous (p=0.005), those with low income, those with chronic diseases (p=0.032), and those with a history of children with congenital diseases (p=0.013). Anxiety scores were higher in pregnant women who used the internet as a source of information about pregnancy (p=0.002), and those who use the internet more (p=0.023). There was a significant positive correlation between STAI (trait) anxiety and PRAQ total score ( r:0.292, p<0.001 ), PRAQ- Fear of giving birth (r:0.145, p=0.024), PRAQ- Worries about bearing a physically or mentally handicapped child (r:0.270, p<0.001), and PRAQ- Concern about own appearance (r:0.254, p=<0.001). Conclusion: Pregnancy-related anxiety was higher in nulliparous, 30-35 age groups, having a chronic disease, husbands' high education status, and having trait anxiety. Information obtained from the internet and the time spent on the internet are associated with increased pregnancy anxiety. Future studies should focus more on predicting factors affecting pregnancy-related anxiety and estimating risks for pregnant women.
Keywords: Anxiety; Pregnancy; Fear; Internet Use